Paperspray Ionization Mass Spectrometry as a Tool for Predicting Real-Time Optimized Dosing of the Chemotherapeutic Drug Melphalan. (13th February 2021) - Zhao, Junfang; Sharat, Chandra; Mehta, Parinda A; Mizuno, Kana; Vinks, Alexander A; Setchell, Kenneth D R
Abstract: Background: Melphalan, an important component of hematopoietic stem cell transplantation (HSCT) preparative regimens, is associated with significant toxicity and large between patient variability in pharmacokinetics making it difficult to calculate the optimal dose for pediatric patients. Paperspray (PS) ionization generates gas phase analyte ions directly from a dried blood spot without the need for prior sample preparation or chromatography. With these advantages, a validated PS–MS/MS assay was developed and applied to the 'real-time' determination of melphalan pharmacokinetics (PK). Methods: Melphalan was quantified by stable-labeled isotope dilution analysis in whole blood by PS–MS/MS. Blood samples were obtained at timed intervals from patients during HSCT after administration of a very low (test) dose of melphalan to avoid toxicity. Pharmacokinetics parameters were calculated using WinNonlin v.6.4. From these data, the optimal therapeutic dose was estimated and full dose PK repeated. Results: PS–MS/MS method was linear over a large dynamic range (25–50 000 ng/mL), intra- and interassay reproducibility of quality control samples was <15% CV. With essentially no prior sample preparation, PS–MS/MS measurement of blood melphalan concentrations showed excellent correlation ( R 2  = 0.959, n  = 62) with a validated electrospray–LC–MS/MS method. Trapezoidal area under the curves calculated for 5 patients administered low dose melphalan showed a high linear correlation ( R 2  = 0.981) between the PS–MS/MS and LC–MS/MS methods. The faster PS approach permitted real-time PK evaluation of individual patients. Conclusions: A validated PS–MS/MS assay for melphalan in patients undergoing HSCT is described that facilitates pharmacokinetic-guided individualized precision dosing with immediate bedside dose adjustments to improve outcomes by balancing toxicity and efficacy of melphalan.